The Used Electrocautery Loop in the Equine Proximal Phalanx - Bouré, L. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
An 18-month-old 420 kg Standardbred colt was admitted for removal of three type I proximal plantar osteochondral fragments of the proximal phalanx. An electrocautery loop probe was used for the arthroscopic removal of the osteochondral fragments. Distension of the metatarsophalangeal joints was achieved using a 1.5% glycine solution. Under arthroscopic guidance, the soft tissue attachments of the osteochondral fragments were transected with the electrocautery loop probe. Once freed of all soft tissue attachments, the fragments were removed with a Ferris-Smith intervertebral disc rongeur. The electrocautery loop probe permitted an easy, precise and smooth dissection of intra-articular soft-tissue structures. Six weeks after the operation, the colt had returned to training. After eight months, the colt remained sound and was racing. The loop electrocautery probe was used as an alternative to manual sharp instruments in the arthroscopic treatment of Type I proximal plantar osteochondral fragments of the proximal phalanx.An electrocautery loop probe was used in the arthroscopic treatment of type I proximal plantar osteochondral fragments of the proximal hind phalanx in a Standardbred horse. The loop electrocautery probe was used as an alternative to manual sharp instruments.
Keywords: Horse; osteochondral fragment; arthroscopy; electrosurgery